2020
DOI: 10.1101/2020.07.23.20160606
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dose-dependent volume loss in subcortical deep grey matter structures after cranial radiotherapy

Abstract: Background and purpose The relation between radiotherapy (RT) dose to the brain and morphological changes in healthy tissue has seen recent increased interest. There already is evidence for changes in the cerebral cortex and white matter, as well as selected subcortical grey matter (GM) structures. We studied this relation in all deep GM structures, to help understand the aetiology of post-RT neurocognitive symptoms. Materials and methods We selected 31 patients treated with RT for glioma. Pre-RT and post-RT … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
(55 reference statements)
2
6
0
Order By: Relevance
“…Rather, change in cognitive performance was observed across several cognitive constructs, including, but not limited to verbal L&M, EF, information processing speed, and fine motor coordination, which have been linked to a wide range of neuroanatomical substrates involving both cortical areas and white matter networks [50-54]. This is supported by previous research indicating morphological changes after brain irradiation in both cortical structures (cortical thickness, gray matter volume, and gray matter density) as well as white matter networks [55-61]. Additionally, the amount of microstructural damage to white matter fibers has been shown to be directly associated with cognitive deterioration in cancer patients [62].…”
Section: Discussionsupporting
confidence: 64%
“…Rather, change in cognitive performance was observed across several cognitive constructs, including, but not limited to verbal L&M, EF, information processing speed, and fine motor coordination, which have been linked to a wide range of neuroanatomical substrates involving both cortical areas and white matter networks [50-54]. This is supported by previous research indicating morphological changes after brain irradiation in both cortical structures (cortical thickness, gray matter volume, and gray matter density) as well as white matter networks [55-61]. Additionally, the amount of microstructural damage to white matter fibers has been shown to be directly associated with cognitive deterioration in cancer patients [62].…”
Section: Discussionsupporting
confidence: 64%
“…Subcortical structures such as hippocampus, amygdala, have also been shown to be vulnerable to volume changes after RT (9, 10). We have repeated these analyses, and observed comparable results (8). Furthermore, we found that in addition to these two structures, the thalamus, globus pallidus, nucleus accumbens, and putamen also show an association between radiotherapy dose and post RT volume loss.…”
Section: Discussionsupporting
confidence: 58%
“…Advances in imaging techniques have allowed the examination of the precise morphological changes in the brain after RT. Changes of white matter (WM) (3), cerebral cortex (47), and subcortical grey matter (GM) structures (810) have already been linked to received dose in several studies. However, these investigations have focused on specific parts or structures of the brain, which may limit the generalizability of the acquired knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…One could argue to score only the untreatable toxicity for example resulting in cognitive decline. Radiation therapy can cause late cognitive decline caused by damaging the brain by several mechanisms such as inducing vascular damage, demyelination and white matter changes to certain parts of the brain [18] , [19] , [20] , [21] . Although recently the OARs identified as possibly being relevant to cognition are expanded, future research needs to show if other areas in the brain should be taken into account and delineated when treating a CNS tumour [20] .…”
Section: Discussionmentioning
confidence: 99%